Merkel Cell Carcinoma on the Forearm: A Case Report and Literature Review - Tan Y; Qi F; Yao A; Zhang Y; Zhang X (Dove Medical Press, 2022)
Yaqi Tan,* Fei Qi,* Amin Yao, Yankun Zhang, Xiuying Zhang Department of Dermatology, Capital Medical University Affiliated Beijing Chao-Yang Hospital, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiuying Zhang, Email zhangxiuying0809@126.comAbstract: Merkel cell carcinoma (MCC) is a rare cutaneous growth with aggressive nature. It mostly affects on the head and neck of white men aged 65 years old and immunosuppressed patients. Limited cases were reported in Asian patients. Loco-regional metastases with the regional lymph nodes involvement were common. The treatment methods include complete surgical excision and radiotherapy. Topical imiquimod and biologics are promising therapies. Here, we present a case of MCC occurring in a 76-year-old Chinese woman.Keywords: Merkel cell carcinoma, skin cancer, carcinoma